Conversational functions of 'I know', 'you know' and 'we know' in collaborative writing of primary school children. Issue 1 (2nd January 2022) - Herder, Anke; Berenst, Jan; de Glopper, Kees; Koole, Tom
ABSTRACT: This paper discusses how primary school students, who are writing together in the context of inquiry learning, explicitly orient to knowing of oneself and others within the peer group. Using Conversation Analysis, we disclose the conversational functions of assertions holding 'I know', 'you know' and 'we know'. First, students position themselves as knowledgeable, to (i) express a preannouncement of a proposal, (ii) respond to a request for information and (iii) reinforce an assertion with use of an evidential. Second, students claim equal epistemic access, as a response to an action that conveys epistemic authority of a peer. Third, students indicate shared knowledge with other participants, to (i) pursue agreement, (ii) check the epistemic status of a co-participant, (iii) reject a proposal for grounds of relevance and (iv) mark shared, newfound knowledge. The different practices are discussed in terms of epistemics in conversation and dialogic writing.